A study on perception of FSPPP students towards the factors contributing to prostitution activities in Malacca City / Nor Azrul Mohd Zin and Izzat Muhaimin Aziz Pauzzi - Mohd Zin, Nor Azrul; Pauzzi, Izzat Muhaimin Aziz (Faculty of Administrative Science and Policy Studies, 2014)
This study examines the perception of Faculty of Administrative Science and Policy Studies (FSPPP) students towards the factors contributing to prostitution activities in Malacca City. A review of literature shows that there are a few factors that contribute to prostitution activities in Malacca City. The studies done by other researchers were used as guideline to determine what factors should be tested in this study and the factors are childhood abuse experiences, peer influences and financial problem. A questionnaire survey was distributed to 181 respondents among the population of FSPPP students. A total of 181 valid respondents were obtained. Data analysis shows that significant relationship exists between three factors and student perception towards the factors contributing to the prostitution activities. Financial problem emerged as the most influencing factor that influence student perception towards the factors contributing to the prostitution activities in Malacca City.